Supernumerary buccal cusp in left maxillary 1st deciduous molar- An unusual case - Ayesha Sameera, Jess Dass Govada, E. Sridhar Reddy, (Journal of Medical Biomedical and Applied Sciences, 2016)
Presence of accessory cusp on the buccal surface of a tooth may occasionally pose problems to dentists. Although its presence may not be a cause for alarm in most instances, nevertheless it can lead to serious consequences if it is damaged. This report describes a rare finding of accessory cusp seen on the buccal surface of the 1st maxillary deciduous Molar and the need for continuous dental surveillance and preventive measures have been highlighted.